Faktor-faktor yang Berhubungan dengan Tindakan Petugas Kesehatan di Puskesmas Kabupaten Kaur dalam Upaya Pencegahan HIV/AIDS - Ahmad Farid Umar; Agustina M.Kes (STIKes Persada Husada Indonesia, 2014)
HIV/AIDS disease causes unrest around the world because of its spread rapidly like geometrical progression, undetectable patients will grow into an iceberg phenomenon, the effective prevention and treatment has not yet been found. In the province of Bengkulu the spread of HIV/AIDS has been sporadic in ten districts/cities and increased rapidly (24.6% per year). In 2012, Bengkulu City Health Department provided two special VCT clinics serving HIV/AIDS free of charge. According to the results of Riskesdas research in 2007 on Community Health Development Index, Kaur District ranked 323 out of 440 districts in Indonesia, and were included in the 150 Troubled Regions districts. Public awareness of HIV/AIDS is still low, 19.2% have correct knowledge about transmission and 21.2% have correct knowledge about prevention. The objective of this study is to determine various factors associated with the actions of the health workers in preventing the spread of HIV/AIDS in Kaur District. This research is a quantitative non-experimental research, the data collected using cross sectional method. There were three research sites being utilize located in the Southem, which are Bintuhan Health Centre (urban area), Linau dan Nasal Health Centres (rural area). Interviews with a structured questionnaires were used to collect the data. The results of this research showed that the actions of Health workers at the three health centers in HIV/AIDS prevention were still very minimum. From a total of 86 respondents, only 17 (19.8%) respondents who were active whereas the majority 69 (80.2%) respondents were categorized not active in HIV/AIDS prevention. Training variable is the most dominant factor affecting health worker actions (p-value=0.000, OR=21.229). Respondents who had participated in the training/workshops/seminars related to HIV/AIDS are 21 times more active in the prevention of HIV/AIDS transmission compared with the health workers who had never attended the training related HIV/AIDS.